1995
DOI: 10.1063/1.360505
|View full text |Cite
|
Sign up to set email alerts
|

Nanometer-scale oxidation of Si(100) surfaces by tapping mode atomic force microscopy

Abstract: The nanometer-scale oxidation of Si(lQ0) surfaces in air is performed with an atomic force microscope working in tapping mode. Applying a positive voltage to the sample with respect to the tip, two kinds of modifications are induced on the sample: grown silicon oxide mounds less than 5 nm high and mounds higher than 10 run (which are assumed to be gold depositions). The threshold voltage necessary to produce the modification is studied as a function of the average tip-to-sample distance. Q 1995 American Instit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(50 citation statements)
references
References 14 publications
0
50
0
Order By: Relevance
“…Due to the larger lattice constant of oxide compared to the metal lattice constant, a thickening of the native oxide layer by LAO induces the creation of nanostructures above the surface. The formation of the nanostructures depends typically on the substrate, the degree of relative humidity [23,24], the tip shape [25], the distance between the tip and the sample [26], the tip velocity (see Fig. 2) and the applied voltage (see Fig.…”
Section: The Local Anodic Oxidation (Lao)mentioning
confidence: 99%
“…Due to the larger lattice constant of oxide compared to the metal lattice constant, a thickening of the native oxide layer by LAO induces the creation of nanostructures above the surface. The formation of the nanostructures depends typically on the substrate, the degree of relative humidity [23,24], the tip shape [25], the distance between the tip and the sample [26], the tip velocity (see Fig. 2) and the applied voltage (see Fig.…”
Section: The Local Anodic Oxidation (Lao)mentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14] Recently this field has experienced a renovated interest. For one side, several results have contributed to an increased understanding of the oxidation mechanism in silicon surfaces 15,16 and its kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…The same tip with a negative bias produced typical LAO patterns on bare regions of the Si substrate (see between points C and D in Fig. 1(b)), where the height is only ~2.5 nm, as expected [24]. Repeated AFM imaging of the region revealed that the raised structures exhibit a time-dependent behavior (Figs.…”
Section: Resultsmentioning
confidence: 84%